Vitreoscilla hemoglobin renders Enterobacter aerogenes highly susceptible to heavy metals - ARMAN, AHMET (SPRINGER, 2004)
When expressed in heterologous microorganisms Vitreoscilla hemoglobin (VHb) acts as oxygen storage and causes a higher oxygen uptake. In this study, the effect of this protein on growth, sensitivity and antioxidant properties of Enterobacter aerogenes exposed to metal stress was investigated. The strain expressing VHb was more sensitive to mercury and cadmium as the minimal inhibitory concentration (MIC) for these metals was up to 2-fold lower in this strain than the host and the recombinant strain carrying a comparable plasmid. At lower concentrations than MIC, the metals partially limited growth and caused an inhibition proportional to metal concentration applied. The growth pattern of VHb expressing strain was also distinctly different from other two non-hemoglobin strains. The hemoglobin containing strain showed substantially higher superoxide dismuates (SOD) activity than the non-hemoglobin strains, while catalase levels were similar in all strains. All strains exposed to copper, however, showed similar MIC values, growth patterns, and SOD and catalase levels.
Keywords: Vitreoscilla hemoglobin; bacterial hemoglobin; oxidative stress; antioxidant systems; catalase; superoxide dismutase; ESCHERICHIA-COLI; SUPEROXIDE-DISMUTASE; CELL-GROWTH; RESISTANCE; BACTERIA; MERCURY; EXPRESSION; IRON; GENE